Utilizing English Songs to Enhance Pronunciation Skills in EFL Learners - A. Yuliana; Sam Hermansyah; Isumarni; Nurul Faradillah (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
This study aimed to investigate the effectiveness of utilizing English songs to enhance pronunciation skills and to examine students interest in learning pronunciation through English songs. The research was conducted using a mixed methods approach at SMPN 1 Panca Rijang in the academic year 2024/2025. A total of 22 ninth-grade students participated in the study. The quantitative data were obtained through pre-test and post-test pronunciation assessments, while the qualitative data were collected from interviews with five students who achieved the highest post-test scores.The quantitative analysis was conducted using descriptive statistics and a paired sample t-test. The result revealed a significant enhancement in students pronunciation scores, with the mean score increasing from 8.18 in the pre-test to 12.91 in the post-test. The mean difference was 4.727, and the t-test analysis produced a t-value of 18.44 and a p-value of 1.89 × 10⁻¹⁴. Since the p-value was far below the significance level of 0.05, the null hypothesis was rejected and the alternative hypothesis was accepted, confirming that the use of English songs significantly enhanced students pronounciation performance. The qualitative findings indicated that showed strong interest and positive responses toward learning pronunciation through songs. They expressed that songs made learning more enjoyable, easier to follow, and more motivating. Some students also mentioned that the rhythm and repetition in songs helped them imitate native like pronunciation more confidently.the findings demonstrate that using English songs in the classroom can both enhance pronunciation skills and foster student interest in pronunciation learning. This suggests that songs can serve as an effective and engaging medium in EFL instruction.